Monday

April 21, 2014

April 21, 2014

Posted by **janet** on Monday, November 26, 2012 at 5:56am.

- math -
**drwls**, Monday, November 26, 2012 at 6:32am2x^2 + 6x +3 = 0

That does not factor into terms with integers. Use the quadratic formula

x= [-b +/-sqrt(b^2-4ac)]/2a

x = [-6 +/-sqrt(36 -24)]/4

= [-6 +/-sqrt12]/4

= -2.366 or -0.634

- math -
**Bosnian**, Monday, November 26, 2012 at 6:58am2 x ^ 2 + 6 x + 3 = 0

Compare your equation to the standard form :

a x ^ 2 + b x + c = 0

and identify the values for a , b , c.

a = 2

b = 6

c = 3

Now evaluate the discriminant :

b ^ 2 - 4 a c = 6 ^ 2 - 4 * 2 * 3 = 36 -

24 = 12

Since b ^ 2 - 4 ac > 0 there are two unequal real solutions:

x1 = [ - b + sqrt ( b ^ 2 - 4 a c ) ] / 2 a

x1 = [ - 6 + sqrt ( 12 ) ] / 2 * 2

x1 = [ - 6 + sqrt ( 4 * 3 ) ] / 4

x1 = [ - 6 + 2 * sqrt ( 3 ) ] / 4

x1 = 2 * [ - 3 + sqrt ( 3 ) ] / 2 * 2

x1 = [ - 3 + sqrt ( 3 ) ] / 2

x1 = [ sqrt ( 3 ) - 3 ] / 2

x1 = - 0.63 approx.

x2 = [ - b - sqrt ( b ^ 2 - 4 a c ) ] / 2 a

x2 = [ - 6 - sqrt ( 12 ) ] / 2 * 2

x2 = [ - 6 - sqrt ( 4 * 3 ) ] / 4

x2 = [ - 6 - 2 * sqrt ( 3 ) ] / 4

x2 = 2 * [ - 3 - sqrt ( 3 ) ] / 2 * 2

x2 = [ - 3 - sqrt ( 3 ) ] / 2

x2 = [ - 3 - sqrt ( 3 ) ] / 2

x2 = - 2.37 approx.

**Related Questions**

math - sol: measuere angle A plus measure angle B plus measure angle c plus ...

math - LOGIC: I plus onehalf of square plus zero plus onehalf of diamond plus ...

MATHS - Prove that one over one squared plus one over two squared plus one over ...

math - insert grouping symbols into the expression 4 plus 3 times 2 squared plus...

math - Have 2 questions: 1. Factor Trinomial competely x^2 + 8x + 53 (reads as x...

algebra - If x+y= 12 and xy equals 50, what does x squared plus y squared equal ...

math - when 3a squared minus 7a plus 6 is subtracted from 4 a squared minus 3a ...

algebra 3 - what is the equation of the line that passes through {negative 4, ...

algebra - what is x squared plus 12x plus 11 equals

Math - 2x cubed minus x squared minus 6x plus 3. I know the answer is (2x-1)(x ...